Integrating A Dialogue Tree Based Turkish Chatbot into an Open Source Python Coding Editor - Bilgin, Turgay Tugay; Yavuz, Erdem (Institute of Electrical and Electronics Engineers Inc., 2022)
In this study, a dialogue tree-based Turkish chatbot has been developed and integreted into the Pynar Python code editor in order to help the users with the questions they may ask while learning the python language. The Pynar Python Code editor is developed as a TÜBİTAK supported open source project. The architecture we propose has been developed in such a way that it can respond to users' questions and give emotional feedback through dialogs and emojis. It also runs completely offline, without being connected to any internet site or web service. The chatbot is coded using Python language and a Turkish NLP library and Qt GUI library. Considering the age and education levels of the target user group of the Pynar editor, our chatbot will provide great convenience to those who are trying to learn Python programming on their own, with the possibility of asking questions and getting answers in their native language. © 2022 IEEE.
3rd International Informatics and Software Engineering Conference, IISEC 2022 -- 2022-12-15 through 2022-12-16 -- Ankara -- 185735
Keywords: Chatbots; Coding Editors; Dialogue Trees